Problematika Pendidikan Kristen dalam Implementasi Pembelajaran di Pusat Kegiatan Belajar Masyarakat - Sarah Wassar; Tabita Margaretha Br. Siahaan (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
Christian education in learning at Community Learning Centres faces the challenges of integrating spiritual values, contextual pedagogy, and the influence of modern digital culture. Learning at Community Learning Centres remains focused on academic and practical skills, meaning that the development of Christian character has not yet been optimally achieved. This study aims to analyse the issues surrounding Christian education and to identify contextual learning strategies to meet the needs of contemporary society. The research employed a descriptive qualitative method through a literature review approach with interpretative analysis of various scholarly works on Christian education. The findings indicate that the implementation of Christian education in PKBMs requires a participatory and contextual pedagogical approach, as well as the strengthening of digital literacy. The study also found that collaboration between educational institutions, churches, families, and the community reinforces the development of learners’ spiritual character. Christian education in PKBM must be developed in an adaptive, inclusive, and transformative manner in line with the needs of a dynamic modern society. Strengthening teachers’ pedagogical competencies is a key factor in improving the quality of sustainable Christian character-based learning. Abstrak Pendidikan Kristen dalam pembelajaran di Pusat Kegiatan Belajar Masyarakat menghadapi tantangan integrasi nilai spiritual, pedagogi kontekstual, serta pengaruh budaya digital modern. Pembelajaran PKBM masih berorientasi akademik dan keterampilan praktis sehingga pembentukan karakter Kristiani belum berjalan optimal. Penelitian ini bertujuan menganalisis problematika Pendidikan Kristen serta menemukan strategi pembelajaran kontekstual bagi kebutuhan masyarakat modern kontemporer. Penelitian menggunakan metode kualitatif deskriptif melalui pendekatan studi pustaka dengan analisis interpretatif terhadap berbagai literatur ilmiah Pendidikan Kristen. Hasil penelitian menunjukkan implementasi Pendidikan Kristen di PKBM memerlukan pendekatan pedagogi partisipatif, kontekstual, serta penguatan literasi digital. Penelitian juga menemukan bahwa kolaborasi lembaga pendidikan, gereja, keluarga, dan masyarakat memperkuat pembentukan karakter spiritual peserta didik. Pendidikan Kristen di PKBM harus dikembangkan secara adaptif, inklusif, dan transformatif sesuai kebutuhan masyarakat modern yang dinamis. Penguatan kompetensi pedagogis guru menjadi faktor penting dalam meningkatkan kualitas pembelajaran berbasis karakter Kristiani berkelanjutan.